Development of a novel cognitive composite outcome to assess therapeutic effects of exercise in the EXERT trial for adults with MCI: The ADAS‐Cog‐Exec - Diane M. Jacobs; Ronald G. Thomas; David P. Salmon; Shelia Jin; Howard H. Feldman; Carl W. Cotman; Laura D. Baker; for the Alzheimer's Disease Cooperative Study EXERT Study Group; for the Alzheimer's Disease Neuroimaging Initiative (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2020)
Abstract Introduction Use of cognitive composites as primary outcome measures is increasingly common in clinical trials of preclinical and prodromal Alzheimer's disease (AD). Composite outcomes can decrease intra‐individual variability, resulting in improved sensitivity to detect longitudinal change and increased statistical power. We developed a novel composite outcome, the ADAS‐Cog‐Exec, for use in the EXERT trial—a Phase 3 randomized, controlled, 12‐month exercise intervention in mild cognitive impairment (MCI). Methods Three combinations of cognitive measures selected from the Alzheimer's Disease Assessment Scale‐Cognitive Subscale version 13 (ADAS‐Cog13), tests of executive function, and the Clinical Dementia Rating (CDR) were created based on previously documented sensitivity to longitudinal change in MCI and to the effects of exercise. Optimally weighted composites of each combination were modeled using data from the ADNI‐1 MCI cohort. Ten‐fold cross‐validation was performed to obtain a bias‐corrected mean to standard deviation ratio (MSDR). The cognitive composites were assessed for their sensitivity to detect 12‐month change in MCI. Results The MSDR of 12‐month change for each of the composite outcomes tested exceeded that of the ADAS‐Cog13 total score. The composite with the highest MSDR (MSDR = 0.48) and associated statistical power included scores on ADAS‐Cog13 Word Recall, Delayed Word Recall, Orientation, and Number Cancellation subtests; Trail‐Making Tests A & B, Digit Symbol Substitution and Category Fluency; and cognitive components of the CDR (Memory, Orientation, Judgement & Problem Solving). Discussion An optimally weighted cognitive composite measure was identified and validated for use in EXERT. This composite contained selected subtests from the ADAS‐Cog13, additional measures of executive function, and box scores for cognitive components of the CDR. Because this composite score demonstrated high sensitivity to longitudinal change in MCI it will be used as the primary outcome measure for the EXERT trial.